2020
DOI: 10.1136/bmjopen-2019-034775
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of myopic maculopathy: a cross-sectional study in Han and Uygur adults in Xinjiang, China

Abstract: ObjectivesTo estimate the prevalence, ethnic differences and associated risk factors of myopic maculopathy in Han and Uygur adults in Xinjiang, China.Design and settingA cross-sectional study with multistage, stratified cluster sampling method was conducted in Xinjiang, China.ParticipantsA total of 4023 Han and Uygur participants aged 40 years and older were eligible for the study.Outcome measuresThe association between myopic maculopathy and its risk factors was screened using the generalised estimating equat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…11,13,18,19,26,29,31,34 In one study, 11 an axial length ≥26 mm was considered high myopia, and in the remaining studies, high myopia was defined as a diopter less than −5 or −6D (based on the author's self-reporting). Eleven studies were conducted in Asia, 11,13,16,18,2733 three in Europe, 17,19,20 one in North America, 26 and one in Oceania. 34 All the studies clarified the definition of MMD.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…11,13,18,19,26,29,31,34 In one study, 11 an axial length ≥26 mm was considered high myopia, and in the remaining studies, high myopia was defined as a diopter less than −5 or −6D (based on the author's self-reporting). Eleven studies were conducted in Asia, 11,13,16,18,2733 three in Europe, 17,19,20 one in North America, 26 and one in Oceania. 34 All the studies clarified the definition of MMD.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 summarizes the basic characteristics of the included studies. Of the 16 studies, 11,13,[16][17][18][19][20][26][27][28][29][30][31][32][33][34] three were written in Chinese, [28][29][30] and the other 13 were written in English. Three studies only reported the prevalence of MMD in patients with high myopia, 20,28,30 five only reported the prevalence of MMD in the general population, 16,17,27,30,32 and eight reported the prevalence of MMD in both the general and high myopia populations.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations